2008
DOI: 10.1007/s00402-008-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

Patella retention versus replacement in total knee arthroplasty; functional and clinimetric aspects

Abstract: The Dynaport Knee Test showed a significant functional advantage for patients with a resurfaced patella [44 vs. 39.7 (P = 0.042)], whereas KSS and The Minimod were not significant (P values ranging from 0.07 to 0.75). Similar to other reports in literature, using the KSS, it was not possible to identify significant difference between patella resurfacing or retaining in total knee arthroplasty, however using a performance based test it was possible to determine significant difference. The found advantage of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Anterior knee pain was the most common complication in the non-resurfaced groups. These results have been supported by other literature suggesting resurfacing of the patella leads to lower rates of revision (Forster 2004, Pakos et al 2005, O'Shea et al 2006, Garneti et al 2008) or increased patient satisfaction (Schroeder-Boersch et al 1998, Mayman et al 2003, Waters and Bentley 2003, Burnett et al 2004, Gildone et al 2005, Parvizi et al 2005, Berti et al 2006, van Hemert et al 2009). Despite promising results, other studies have suggested that resurfacing of the patella does not change rates of revision, patient satisfaction, or clinical outcome (Grace and Sim 1988, Healy et al 1995, Robertsson et al 2000, Wood et al 2002, 2005, Burnett et al 2004, 2007, Campbell et al 2006, Myles et al 2006, Oztürk et al 2006, Smith et al 2006, 2008, Epinette and Manley 2008).…”
Section: Introductionsupporting
confidence: 76%
“…Anterior knee pain was the most common complication in the non-resurfaced groups. These results have been supported by other literature suggesting resurfacing of the patella leads to lower rates of revision (Forster 2004, Pakos et al 2005, O'Shea et al 2006, Garneti et al 2008) or increased patient satisfaction (Schroeder-Boersch et al 1998, Mayman et al 2003, Waters and Bentley 2003, Burnett et al 2004, Gildone et al 2005, Parvizi et al 2005, Berti et al 2006, van Hemert et al 2009). Despite promising results, other studies have suggested that resurfacing of the patella does not change rates of revision, patient satisfaction, or clinical outcome (Grace and Sim 1988, Healy et al 1995, Robertsson et al 2000, Wood et al 2002, 2005, Burnett et al 2004, 2007, Campbell et al 2006, Myles et al 2006, Oztürk et al 2006, Smith et al 2006, 2008, Epinette and Manley 2008).…”
Section: Introductionsupporting
confidence: 76%
“…If more objective assessment tools are used, impalpable differences between resurfacing and nonresurfacing might be found. In a recent study, Hemert et al [5] used the Dynaport knee test and the Minimod gait test to assess the function of the knee after TKA. The Dynaport knee test showed a significant functional advantage for patients with a resurfaced patella, while knee society score (KSS) did not.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since patella resurfacing was introduced, research and discussion on resurfacing patella were increasing. Recent meta-analysis or evidence-based analysis has reached a consensus [1][2][3][4] , although there is a tendency to resurface the patella in patients with inflammatory arthritis [5] , whether the patella should be resurfaced for the primary TKA is still controversial for the time being.…”
Section: Introductionmentioning
confidence: 99%
“…Also, knee scores may not capture existing differences equally [37]. Moreover, the subvastus approach might not result in better tissue sparing, as it may harm viable structures [5, 24].…”
Section: Introductionmentioning
confidence: 99%